Experience in Managing Severe Malnutrition in a Government Tertiary Treatment Facility in Bangladesh - Hossain, Md Iqbal; Dodd, Nina S; Ahmed, Tahmeed; Miah, Golam Mothabbir; Jamil, Kazi M; Nahar, Baitun; Alam, Badrul; Mahmood, CB (Journal of Health, Population and Nutrition, 2009)
Children with severe acute malnutrition, defined as weight-for-height <70% of the reference median or bilateral pedal oedema or mid-arm circumference <110 mm having complications, were managed in the Nutrition Unit of the Chittagong Medical College Hospital (CMCH) following the guidelines of the World Health Organization, with support from Concern Worldwide Bangladesh and ICDDR,B. In total, 171 children aged less than five years (mean±SD age 23.5±15.3 months) were admitted during June 2005-May 2006. Of them, 66% were aged less than two years, and 84.2% belonged to households with a monthly income of less than US 40. The main reason for bringing children by their families to the hospital was associated major illnesses: bronchopneumonia (33%), oedema (24%), diarrhoea (11%), pulmonary tuberculosis (9%), or other conditions, such as meningitis, septicaemia, and infections of the skin, eye, or ear. The exit criteria from the Nutrition Unit were: (a) for children admitted without oedema, an absolute weight gain of ≥500 and ≥700 g for children aged less than two years and 2-5 years respectively; and for children admitted with oedema, complete loss of oedema and weight-for-height >70% of the reference median, and (b) the mother or caretaker has received specific training on appropriate feeding and was motivated to follow the advice given. Of all the admitted children, 7.6% of parents insisted for discharging their children early due to other urgent commitments while 11.7% simply left with their children against medical advice. Of the 138 remaining children, 88% successfully graduated from the Nutrition Unit with a mean weight gain of 10.6 g/kg per day (non-oedematous children) and loss of -1.9 g/kg per day (oedematous children), 86% graduated in less than three weeks, and the case-fatality rate was 10.8%. The Nutrition Unit of CMCH also functions as a training centre, and 197 health functionaries (82 medical students, 103 medical interns, and 12 nurses) received hands-on training on management of severe malnutrition. The average cost of overall treatment was US 14.6 per child or approximately US 1 per child-day (excluding staff-cost). Food and medicines accounted for 42% and 58% of the total cost respectively. This study demonstrated the potential of addressing severe acute malnutrition (with complications) effectively with minimum incremental expenditure in Bangladesh. This public-private approach should be used for treating severe acute malnutrition in all healthcare facilities and the treatment protocol included in the medical and nursing curricula. Key words: Child nutrition; Child nutrition disorders; Healthcare cost; Infant nutrition; Infant nutrition disorders; Oral rehydration therapy; Severe acute malnutrition; Standardized protocol; Bangladesh doi: 10.3329/jhpn.v27i1.3319 J Health Popul Nutr 2009 Feb;27(1):72-80